COVID‐19‐associated subacute invasive pulmonary aspergillosis. Issue 1 (29th September 2021) - Swain, Satish; Ray, Animesh; Sarda, Radhika; Vyas, Surabhi; Singh, Gagandeep; Jorwal, Pankaj; Kodan, Parul; Khanna, Puneet; Xess, Immaculata; Sinha, Sanjeev; Wig, Naveet; Trikha, Anjan
Abstract: Background: Though invasive pulmonary aspergillosis is a well known complication of COVID‐19 pneumonia, indolent forms of aspergillosis have been rarely described. Methods: We prospectively collected the clinico‐radio‐microbiological data of 10 patients of subacute invasive pulmonary aspergillosis (SAIA), who presented to our hospital with recent history of COVID‐19 pneumonia along with cavitary lung disease, positive IgG (against Aspergillus ) with or without positive respiratory samples for Aspergillus spp . Result: The mean age of presentation of SAIA was 50.7 ± 11.8 years. All the patients had recently recovered from severe COVID‐19 illness with a mean duration of 29.2 ± 12 days from COVID‐19 positivity. Cough was the predominant symptom seen in 8/10 (80%) patients followed by haemoptysis. 7/10 (70%) patients were known diabetic. While serum galactomannan was positive in 5/9 patients (55.5%), fungal culture was positive in 2/7 patients (28.5%) and polymerase chain reaction (PCR) for Aspergillus was positive in three patients. Eight (80%) patients presented with a single cavitary lesion; pseudoaneurysm of pulmonary artery was seen in two patients and post‐COVID‐19 changes were seen in all patients. All patients were treated with voriconazole, out of which four (40%) patients died during the follow‐up period. Conclusion: SAIA should be considered in the differential diagnosis of cavitating lung lesions in patients with recent history of COVID‐19 in the background of steroid use with or without pre‐existing diabetes.